PERK-eIF2α-ERK1/2 axis drives mesenchymal-endothelial transition of cancer-associated fibroblasts in pancreatic cancer. (1st September 2021) - Cai, Wenrun; Sun, Xugang; Jin, Fanjie; Xiao, Di; Li, Hui; Sun, Huizhi; Wang, Yifei; Lu, Yang; Liu, Jing; Huang, Chongbiao; Wang, Xiuchao; Gao, Song; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by remarkable desmoplasia, usually driven by cancer-associated fibroblasts (CAFs), influencing patient prognosis. CAFs are a group of plastic cells responsible for tumor growth and metastasis. Fibroblasts have been reported to directly contribute to angiogenesis by undergoing mesenchymal-endothelial transition (MEndoT) after ischemic injury in the heart, brain, and hindlimbs. However, whether CAFs can undergo similar transdifferentiation in the hostile tumor microenvironment and directly contribute to tumor angiogenesis remains unclear. Herein, we provide evidence that CAFs can adopt an endothelial cell-like phenotype and directly contribute to tumor angiogenesis in vitro and in vivo . Furthermore, this program is regulated by the PERK-eIF2α-ERK1/2 axis. Pharmacological inhibition of PERK with GSK2606414 limited the phenotypic transition of CAFs. In conclusion, our results suggest that CAFs contribute to tumor angiogenesis by undergoing the MEndoT, thus representing therapeutic targets for improving PDAC prognosis. Highlights: CAFs in PDAC can adopt an endothelial phenotype in vitro and in vivo. UPR activation is essential for MEndoT induction in CAFs. The PERK-eIF2α-ERK1/2 signaling branch regulates CAF MEndoT. PERK inhibition suppresses tumor MEndoT and enhances the chemotherapeutic efficacy of gemcitabine.